2017
DOI: 10.3390/ijerph14111337
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Investment and Health Costs in Roma Women

Abstract: In this paper, we examine whether variation in reproductive investment affects the health of Roma women using a dataset collected through original anthropological fieldwork among Roma women in Serbia. Data were collected in 2014–2016 in several Roma semi-urban settlements in central Serbia. The sample consisted of 468 Roma women, averaging 44 years of age. We collected demographic data (age, school levels, socioeconomic status), risk behaviors (smoking and alcohol consumption), marital status, and reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…In this sample, the observed mean age at first marriage was 17, while the mean age at first reproduction was at an optimum of 18 years. Previous studies on the Roma reproductive pattern found that Roma women start reproducing at the optimum age, continue having children in their most fertile years and cease reproduction relatively early, with later age at first reproduction being significantly associated with infant low birth weight (20,30) . The risks associated with later maternal age at first reproduction include changes in children's quantity but also quality, suggesting a significant disadvantage of delayed age at first reproduction (21,(42)(43)(44) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this sample, the observed mean age at first marriage was 17, while the mean age at first reproduction was at an optimum of 18 years. Previous studies on the Roma reproductive pattern found that Roma women start reproducing at the optimum age, continue having children in their most fertile years and cease reproduction relatively early, with later age at first reproduction being significantly associated with infant low birth weight (20,30) . The risks associated with later maternal age at first reproduction include changes in children's quantity but also quality, suggesting a significant disadvantage of delayed age at first reproduction (21,(42)(43)(44) .…”
Section: Discussionmentioning
confidence: 93%
“…Cross-culturally the greatest risk is concentrated only in the youngest of mothersgenerally those younger than 15 years -, with the risk being lowest for first births (17)(18) . Yet, despite the costs, there may also be fitness benefits associated with early reproduction, such as the advantage of longer reproductive periods and higher fertility [19][20] . By contrast, however, the cost of delayed onset of reproduction is associated with fewer descendants, a shorter reproductive period, longer generation times, unfavorable child outcomes, greater risk of reproductive failure and a higher cumulative mortality risk (21)(22)(23) .…”
Section: Introductionmentioning
confidence: 99%
“…Among the complex negative factors accompanying underdevelopment, unwanted children may be the most serious, as being unwanted, in addition to low birthweight and high neonatal mortality risk, may have a long-lasting effect on a child’s development, and is associated with adverse life cycle outcomes [ 62 ]. Very few Roma women use modern contraceptives, but the majority cease reproduction in their late twenties, with an average of four surviving children, implying that together with their partners, they make a deliberate decision to stop reproducing after the desired number of children is reached [ 63 ]. There was no difference in wantedness between the third and fourth born children, suggesting that factors other than desired number of children might influence child wantedness.…”
Section: Discussionmentioning
confidence: 99%
“…Additional variables were used to account for maternal and child conditions, based on the existing literature (Čvorović & Coe, 2017). Whether a mother (N = 130) ever had a child who later died was used as a proxy for child mortality.…”
Section: Methodsmentioning
confidence: 99%
“…The Roma, a diverse population of South Asian origin, are the largest ethnic minority in Europe, experiencing severe social exclusion, poverty, welfare dependency, poor health, and higher levels of fertility, child mortality and low offspring birthweight rates than observed in other ethnic groups or majority populations (Balázs et al, 2014). Roma women living in Serbia lack education, the skills for and access to jobs, and have cultural practices that seem to limit women's choices (Čvorović & Coe, 2017). Typically, Roma girls enter traditionally arranged marriage and motherhood as teenagers while high fertility is culturally encouraged (Čvorović, 2014).…”
Section: Introductionmentioning
confidence: 99%